Secularism and religion-making - Dreßler, Markus; Mandair, Arvind-Pal ca. 20./21. Jh. (Reflection and theory in the study of religion series, 2011)
"This book conceives of "religion-making" broadly as the multiple ways in which social and cultural phenomena are configured and reconfigured within the matrix of a world-religion discourse that is historically and semantically rooted in particular Western and predominantly Christian experiences, knowledges, and institutions. It investigates how religion is universalized and certain ideas, social formations, and practices rendered "religious" are thus integrated in and subordinated to very particular - mostly liberal-secular - assumptions about the relationship between history, politics, and religion. The individual contributions, written by a new generation of scholars with decisively interdisciplinary approaches, examine the processes of translation and globalization of historically specific concepts and practices of religion - and its dialectical counterpart, the secular - into new contexts. This volume contributes to the relatively new field of thought that aspires to unravel the thoroughly intertwined relationships between religion and secularism as modern concepts."--Provided by publisher